Sleep habits in German athletes before important competitions or games - Erlacher, D.; Ehrlenspiel, F.; Adegbesan, O. A.; Galal El-Din, H. (Journal of Sports Sciences, 2011)
Sleep is generally regarded as a valuable resource for psychological and physiological well-being. Although the effects of sleep on athletic performance have been acknowledged in sport science, few studies have investigated the prevalence of sleep problems and their effects on elite athletes before a sport event. In this study, 632 German athletes from various sports were asked about their sleep habits during the night(s) before an important competition or game. The findings indicate that 65.8% of the athletes experienced poor sleep in the night(s) before a sports event at least once in their lives and a similarly high percentage (62.3%) had this experience at least once during the previous 12 months. Athletes of individual sports reported more sleep difficulties than athletes of team sports. The main sleep problem was not being able to fall asleep. Internal factors such as nervousness and thoughts about the competition were rated highest for causing sleep problems. Most athletes stated that disturbed sleep had no influence on their athletic performance; however, athletes also reported effects such as a bad mood the following day, increased daytime sleepiness, and worse performance in the competition or game. The differences between individual and team sports indicate that athletes in some sports need more help than those in other sports in managing sleep problems.